Synergization of ductility and yield strength in a dilute quaternary Mg-Zn-Gd-Ca alloy through texture modification and Guinier–Preston zone. (15th January 2022) - Yan, H.; Shao, X.H.; Li, H.P.; Chen, R.S.; Cui, H.Z.; Han, En-Hou
Abstract: Mg-Zn-RE alloy sheets usually have a transverse direction (TD)-split non-basal texture and low yield strength and poor disperse hardening effect. To explore the synergization of ductility and yield strength of magnesium sheet via texture and nano-precipitates modification, we designed a dilute quaternary Mg-0.8Zn-0.3Gd-0.2Ca (wt.%) alloy and applied hot-rolling and heat treatment to obtain a good balance of ductility and yield strength. The rolled heat-treated sheet has a special circular non-basal texture and fine Mg2 Zn3 Gd2 particles with the size of ∼100 nm and monolayer ordered Guinier-Preston (G.P.) zone enriched with Ca and Zn atoms along the basal plane with full coherency. A good combination of elongation and yield strength was achieved in this dilute alloy sheet with elongation of 40% both along the rolling direction (RD) and transverse direction and yield strength of 130 MP at room temperature, mainly attributed to the dispersion strengthening from monolayer G.P. zone and the circular non-basal texture. Graphical abstract: Image, graphical abstract